Alanine scan of the opioid peptide dynorphin B amide - Joshi, Anand A. (Biopolymers, 2017)
To date structure-activity relationship (SAR) studies of the dynorphins (Dyn), endogenous peptides for kappa opioid receptors (KOR), have focused almost exclusively on Dyn A with minimal studies on Dyn B. While both Dyn A and Dyn B have identical N-terminal sequences, their C-terminal sequences differ which could result in differences in pharmacological activity. We performed an alanine scan of the non-glycine residues up through residue 11 of Dyn B amide to explore the role of these side chains in the activity of Dyn B. The analogs were synthesized by fluorenylmethyloxycarbonyl (Fmoc)-based solid phase peptide synthesis and evaluated for their opioid receptor affinities and opioid potency and efficacy at KOR. Similar to Dyn A the N-terminal Tyr(1) and Phe(4) residues of Dyn B amide are critical for opioid receptor affinity and KOR agonist potency. The basic residues Arg(6) and Arg(7) contribute to the KOR affinity and agonist potency of Dyn B amide, while Lys(10) contributes to the opioid receptor affinity, but not KOR agonist potency, of this peptide. Comparison to the Ala analogs of Dyn A(1-13) suggests that the basic residues in the C-terminus of both peptides contribute to KOR binding, but differences in their relative positions may contribute to the different pharmacological profiles of Dyn A and Dyn B. The other unique C-terminal residues in Dyn B amide also appear to influence the relative affinity of this peptide for KOR. This SAR information may be applied in the design of new Dyn B analogs that could be useful pharmacological tools.